IL-33/ST2 Pathway and Classical Cytokines in End-Stage Heart Failure Patients Submitted to Left Ventricular Assist Device Support: A Paradoxic Role for Inflammatory Mediators? - C. Caselli; A. D'Amico; R. Ragusa; R. Caruso; T. Prescimone; M. Cabiati; S. Nonini; P. Marraccini; S. Del Ry; M. G. Trivella; O. Parodi; D. Giannessi (Mediators of Inflammation)
Background. Inflammation is a critical process contributing to heart failure (HF). We hypothesized that IL-33/ST2 pathway, a new mechanism regulated during cardiac stress, may be involved in the functional worsening of end-stage HF patients, candidates for left ventricular assist device (LVAD) implantation, and potentially responsible for their outcome. Methods. IL-33, ST2, and conventional cytokines (IL-6, IL-8, and TNF-α) were determined in cardiac biopsies and plasma of 22 patients submitted to LVAD implantation (pre-LVAD) and compared with (1) control stable chronic HF patients on medical therapy at the moment of heart transplantation without prior circulatory support (HT); (2) patients supported by LVAD at the moment of LVAD weaning (post-LVAD). Results. Cardiac expression of ST2/IL-33 and cytokines was lower in the pre-LVAD than in the HT group. LVAD determined an increase of inflammatory mediators comparable to levels of the HT group. Only ST2 correlated with outcome indices after LVAD implantation. Conclusions. IL-33/ST2 and traditional cytokines were involved in decline of cardiac function of ESHF patients as well as in hemodynamic recovery induced by LVAD. IL-33/ST2 pathway was also associated to severity of clinical course. Thus, a better understanding of inflammation is the key to achieving more favorable outcome by new specific therapies.